CHARGE Syndrome: An Indonesian Case Report - Jessica Juan Pramudita; Agustini Utari; Tri Indah Winarni; Sultana MH Faradz (Journal of Biomedicine and Translational Research, 2017)
Background: CHARGE syndrome is an autosomal dominant congenital and rare genetic disease.The prevalence of CHARGE syndrome approximately 1:12,000 births.In the previous study, the CHD7 gene mutation is responsible in about 2/3 cases of CHARGE syndrome.  The syndrome associations consist of C-coloboma of the eyes, H-heart disease, A-atresia of the choanae, R-retarded growth and development, G-genital hypoplasia/genitourinary anomalies and E-ear anomalies and/or hearing loss. All defects are not seen in every case and a different spectrum of associations is seen in most of the cases.Method: Case was undergone physical examination by experience pediatricians, pedigree construction, and other diagnostic procedure (X-ray, echocardiography, and multi slice computer tomography (MSCT) scan).Results: A boy aged 2 years 9 months with clinical features with match major and minor criterias of CHARGE syndrome.